Scoping the Utility of Lentiviruses as an Aid in Oncologic Treatment and Vaccine Development: A Narrative Review - Aayush (Bangladesh Journal of Infectious Diseases, 2025)
Lentiviruses have emerged as the “go-to” when it comes to viral vectors. Their capacity to effectively introduce therapeutic genes into specific cells, such as cancer cells, is extremely promising. The review also looks at the use of lentiviruses in the creation of innovative vaccines. Researchers hope to trigger a strong immune response against cancer cells by encoding tumour-associated antigens or immune stimulatory chemicals into the viral vector. The possible benefits and difficulties of using lentiviruses in various fields are carefully evaluated. They have a high capacity to deliver large antigens and have low anti-vector immunity, making them an attractive choice for immunizations targeting various cancers and infectious diseases. Ultimately, the study clarifies future approaches and existing research endeavours aimed at maximising lentiviral vectors' potential for cancer medicines and vaccines. Bangladesh Journal of Infectious Diseases, December 2024;11(2):152-159